L’intelligenza artificiale applicata al patrimonio culturale: Una innovazione tecnologica per la conservazione e la valorizzazione del patrimomio culturale - Papi, Luca; Petrillo, Antonella (Archeomatica, 2023)
Artificial intelligence (AI) represents a promising frontier for cultural heritage, offering new perspectives for conservation, cataloguing, research and valorisation. AI can allow us to preserve and pass on our cultural roots to future generations. However, a "balanced" approach is needed, in which technological innovation is embraced while preserving the integrity and value of the works of art and of history itself. With careful management, artificial intelligence can become a valuable tool for preserving and enhancing our cultural heritage for future generations. What are the benefits, challenges and future developments of AI in the context of cultural heritage?